2008
DOI: 10.1111/j.1939-165x.2008.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation values in normal ferrets (Mustela putorius furo) using selected methods and reagents

Abstract: Background: Accurate determination of commonly measured coagulation values would be useful in the diagnosis and management of coagulopathies in domestic ferrets (Mustela putorius furo). We are unaware of reports of coagulation times in this species. Objectives: The purpose of this study was to determine reference values for prothrombin time (PT), activated partial thromboplastin time (PTT), fibrinogen concentration, and antithrombin (AT) activity in ferrets using selected methods and reagents. Methods: Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
3
15
1
Order By: Relevance
“…The ferret PT and aPTT values found in our study were similar to the previously reported reference values for ferrets [1,8]. However, the ferret fibrinogen value (486.7 ± 97.9 mg/dl) detected in our study was quite different from the previously reported value (107.4 ± 19.8 mg/dl) [1]. This discrepancy might have been due to the different assays used because the fibrinogen measurement was performed with the PT-fibrinogen method using a photo-optic analyzer in the previous report [1] and by the Clauss method with an electro-mechanical analyzer in our study.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The ferret PT and aPTT values found in our study were similar to the previously reported reference values for ferrets [1,8]. However, the ferret fibrinogen value (486.7 ± 97.9 mg/dl) detected in our study was quite different from the previously reported value (107.4 ± 19.8 mg/dl) [1]. This discrepancy might have been due to the different assays used because the fibrinogen measurement was performed with the PT-fibrinogen method using a photo-optic analyzer in the previous report [1] and by the Clauss method with an electro-mechanical analyzer in our study.…”
supporting
confidence: 91%
“…system. The ferret PT and aPTT values found in our study were similar to the previously reported reference values for ferrets [1,8]. However, the ferret fibrinogen value (486.7 ± 97.9 mg/dl) detected in our study was quite different from the previously reported value (107.4 ± 19.8 mg/dl) [1].…”
supporting
confidence: 66%
See 2 more Smart Citations
“…The effective dose at which 50% of ferrets exhibited an emetic response to radiation is similar to that of humans (Sanzari et al 2013). Data from the ferret studies have been used to develop a mathematical model for the human emetic response to radiation as well as to identify the dopaminergic mechanisms that play a minor role in radiation-induced emesis in the ferret (Benson et al 2008).…”
Section: Ferretmentioning
confidence: 99%